Your super quick guide to Learning Online - Salmons ,Janet E. (London: SAGE, 2021)
"Get on the right track from day one at university with this super quick guide. Full of top tips and hints for everything university can throw at you - from living away from home to doing your own research - this book helps you: Ace your assignments with essential checklists Beat procrastination with tools for time management Tackle writing problems with a toolkit of quick fixes Get smart about managing your money Look after your mental health and well-being Prepare for work with CV tips and careers guidance An indispensable guide to get you through university cool, calm and in control!"--
Keywords: Learning Online